The Traditional Chinese Medicine Compound Huangqin Qingre Chubi Capsule Inhibits the Pathogenesis of Rheumatoid Arthritis Through the CUL4B/Wnt Pathway - Wang, Xiao; Chang, Jun; Zhou, Guoliang; Cheng, Chenglong; Xiong, Youyi; Dou, Jinfeng; Cheng, Gen; Miao, Chenggui (Frontiers in Pharmacology, 2021)
The pathogenesis of rheumatoid arthritis (RA) is still not fully clarified, and the development of therapeutic drugs for RA is particularly urgent. Our group studies a possibility that circ_ 0015756/miR-942-5p may participate in the pathogenesis of RA through disordered Cullin 4B (CUL4B) and the traditional Chinese medicine compound Huangqin Qingre Chubi Capsule (HQC) may inhibit the pathogenesis of RA through the CUL4B/Wnt pathway. Data showed that the expression of circ_0015756 increased not only in fibroblast-like synoviocytes (FLS) of RA, but also in synovium and FLS of CIA mice, and the expression of miR-942-5p decreased. Abnormal circ_0015756 up-regulated the CUL4B expression and activated the canonical Wnt signaling pathway by inhibiting the expression of miR-942-5p. Circ_0015756 participated in the pathogenesis of RA and promoted the abnormal proliferation of FLS. Further, circ_0015756 activated the secretion of IL-1 and IL-8 and promoted the production of RA pathological gene MMP3 and fibronectin. Further analysis showed that HQC inhibited the pathogenesis of RA through the CUL4B/Wnt pathway, and the specific target was CUL4B. HQC interfered with the effects of circ_0015756 on the pathogenesis of RA by inhibiting the CUL4B, showing a good therapeutic effect on RA.